The contents of vitamin d and antimicrobial peptides with acute inflammatory bacterial diseases of the bronchopulmonary system in children of early age - Kraynya, H. V.; Крайня, Ганна Вікторівна (My University, 2019)
Development of acute inflammatory bacterial diseases of a bronchopulmonary system in children of early age happens against the background of deficiency of vitamin D which occupies an important role in thin balance between protective immunity and an immunopathology. The imbalance in the system of synthesis of antimicrobic peptides associated with insufficiency of vitamin D leads to decrease in immunoreactivity of an epithelium of respiratory tracts that in turn leads to massive colonization by bacterial pathogens.
Keywords: тези